Small Molecular Prodrug Amphiphile Self-Assembled AIE Dots for Cancer Theranostics - Yang, Xing; Luo, Yuan; Li, Sanpeng; Xu, Xiuli; Bao, Yingxia; Yang, Jiaming; Ouyang, Defang; Fan, Xingxing; Gong, Ping; Cai, Lintao (Frontiers in Bioengineering and Biotechnology, 2020)
A simple and facile one-step method was developed to construct a small molecular prodrug amphiphile self-assembled organic dots CPPG with aggregation-induced emission (AIE) characteristics. Diphenylalanine peptide (FF), which is the essential moiety of the self-assembling peptide-drug conjugate and as its core recognition motifs for molecular self-assembly. In addition, the D-glucose transported protein (GLUT), which is one of the important nutrient transporters and is overexpressed in cancer cells. The conjugation of glycosyl further endues the nanoparticle with good biocompatibility and tumor-targeting ability. Taking advantages of both the cancer cell-targeting capability of small molecular prodrug amphiphile CPPG and the AIE aggregates with strong emission, the prepared CPPG AIE dots can target cancer cells specifically and inhibit the proliferation of cancer cells with good biocompatibility and photostability. Based on the general approach, types of universal organic fluorescent nanoprobes could be facilely constructed for imaging applications and biological therapeutics, which possess the properties of specific recognition and high brightness.